Effects of different stagnant meteorological conditions on aerosol chemistry and regional transport changes in Beijing, China. (1st August 2021) - Li, Jiayun; Gao, Wenkang; Cao, Liming; He, Lingyan; Zhang, Xinghua; Yan, Yingchao; Mao, Jia; Xin, Jinyuan; Wang, Lili; Tang, Guiqian; Liu, Zirui; Ji, Dongsheng; et al.
Abstract: To study the aerosol chemistry and regional transport changes in Beijing under different stagnant meteorological conditions, a simultaneous combined observation of the nonrefractory submicron aerosol (NR-PM1 ) chemical compositions and vertical wind profiles was conducted at an urban site (Beijing) and a regional background site (Xinglong) in the North China Plain (NCP) from November 2018 to January 2019. The backward trajectories of PM1 species in Beijing under different pollution stages were calculated. The results showed that the proportion of backward trajectories from southern regions increased from 0% in the clean stage (PM1  < 35 μg m −3 ) to 47% in the pollution stage (PM1  > 75 μg m −3 ), suggesting the aerosol pollution in winter Beijing was greatly affected by regional transport from southern regions. Although the proportion of trajectories from the northwestern regions of Beijing decreased from the clean stage to the pollution stage, the trajectories still comprised a large proportion (53%), which indicates that the northwestern air mass can also cause heavy pollution in winter. Therefore, two typical episodes with air masses from the southwest (episode 1) and northwest (episode 2) regions were selected for further study. The results showed that episode 1 in Beijing lasted for several days and was initiated by regional transport and dominated by heterogeneous reactions, while episode 2 was dominated by rapid regional transport in a short time. Both water vapor and pollutants were transported from southern regions in episode 1, while only pollutants were transported in episode 2. Because of the stronger heterogeneous reactions in episode 1, inorganic aerosols in Beijing accounted for 71% of PM1 in episode 1, which was higher than that in episode 2 (56%). In addition, the transport of water vapor from southern China enhanced the secondary aerosol formation in Xinglong and expanded the scope of regional pollution. In comparison, the systematic south wind did not reach the background area in episode 2. Correspondingly, the PM1 concentration in Beijing was 62% higher than that in Xinglong in episode 2, which was much higher than that in episode 1 (11%). Our results showed that in addition to the enhancement of heterogeneous reactions caused by the increase in humidity, the rapid transport of pollutants because of the sudden change of wind field from north to south can also dominant heavy haze episodes in winter Beijing. Highlights: Haze pollution in Beijing was affected by regional transport from southern regions. Heterogeneous reactions dominate haze episode with air masses from southern regions. Rapid transportation of pollutants dominates the explosive growth of pollutants.